Boltzmann Thermometry in Cr3+‐Doped Ga2O3 Polymorphs: The Structure Matters!. Issue 9 (24th February 2021) - Back, Michele; Ueda, Jumpei; Nambu, Hiroshi; Fujita, Masami; Yamamoto, Akira; Yoshida, Hisao; Tanaka, Hiromitsu; Brik, Mikhail G.; Tanabe, Setsuhisa
Abstract: The performance of luminescent Cr 3+ ‐doped thermometers is strongly influenced by the locally surrounding ligand field. A universal relationship between the thermometric performance and structural/chemical parameters is highly desirable to drive the development of effective Cr 3+ ‐based thermal sensors avoiding trial‐and‐error procedures. In this view, as prototypes, the electronic structure and the thermometric performance of Cr 3+ ‐doped α‐Ga2 O3 and β‐Ga2 O3 polymorphs are compared. Combining a detailed theoretical and spectroscopic investigation, the electronic configuration and the crystal field (CF) acting on the Cr 3+ in α‐Ga2 O3 are described for the first time and compared with β‐Ga2 O3 :Cr 3+ polymorph to discuss the thermometric behavior. A linear relationship between the 4 T2 – 2 E energy gap (directly linked to the relative sensitivity) and the CF strength Dq is demonstrated for a wide variety of materials. This trend can be considered as a first step to set guiding principles to design effective Cr 3+ ‐based Boltzmann thermometers. In addition, as a proof of concept, particles of β‐Ga2 O3 :Cr 3+ thermometer are used to locally measure in operando thermal variations of Pt catalysts on β‐Ga2 O3 :Cr 3+ support during a catalytic reaction of C2 H4 hydrogenation in a contactless and reliable mode, demonstrating their real potentials. Abstract : A universal relationship between the thermal resolution and the crystal field strength of Cr 3+ ‐activated phosphors is introduced to predict the performance of Cr 3+ ‐based contactless thermometers based on the Boltzmann law. β‐Ga2 O3 :Cr 3+ is used as support for Pt to probe in situ the real catalyst temperature during C2 H4 hydrogenation, showing a remarkable and highly reliable performance.